2007
DOI: 10.1093/brain/awm121
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain functional connectivity in the early blind

Abstract: Early visual deprivation can lead to changes in the brain, which may be explained by either of two hypotheses. The general loss hypothesis has been proposed to explain maladjustments, while the compensatory plasticity hypothesis may explain a superior ability in the use of the remaining senses. Most previous task-based functional MRI (fMRI) studies have supported the compensatory plasticity hypothesis, but it has been difficult to provide evidence to support the general loss hypothesis, since the blind cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
210
5
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(250 citation statements)
references
References 86 publications
(138 reference statements)
31
210
5
4
Order By: Relevance
“…A finding that initially seems at odds with our data is that Liu et al (2007) and Yu et al (2008) reported decreased functional connectivity [i.e., correlations of the BOLD signal between brain regions (Friston et al, 1993)] in blind volunteers compared with controls between visual and auditory cortical areas during resting-state fMRI. However, if one considers that the visual cortex can also be activated by auditory stimuli in sighted if the task requires high levels of attention (Cate et al, 2009), the results seem more alike: possibly, the visual cortex of blind people is predominantly recruited during demanding tasks or when relevant information is supplied (Röder et al, 1996).…”
Section: Figurecontrasting
confidence: 96%
See 2 more Smart Citations
“…A finding that initially seems at odds with our data is that Liu et al (2007) and Yu et al (2008) reported decreased functional connectivity [i.e., correlations of the BOLD signal between brain regions (Friston et al, 1993)] in blind volunteers compared with controls between visual and auditory cortical areas during resting-state fMRI. However, if one considers that the visual cortex can also be activated by auditory stimuli in sighted if the task requires high levels of attention (Cate et al, 2009), the results seem more alike: possibly, the visual cortex of blind people is predominantly recruited during demanding tasks or when relevant information is supplied (Röder et al, 1996).…”
Section: Figurecontrasting
confidence: 96%
“…However, if one considers that the visual cortex can also be activated by auditory stimuli in sighted if the task requires high levels of attention (Cate et al, 2009), the results seem more alike: possibly, the visual cortex of blind people is predominantly recruited during demanding tasks or when relevant information is supplied (Röder et al, 1996). This would explain why resting-state studies (no attentional demands) failed to find coupling (Liu et al, 2007;Yu et al, 2008), whereas activation-based effective-connectivity studies did find enhanced coupling in the blind (Fujii et al, 2009;present study). This hypothesis is also backed by studies that found attentional modulations of visual cortex activity in the blind (Liotti et al, 1998;Stevens et al, 2007).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus the interruption of synaptic elimination by early visual deprivation may prevent the visual cortex from thinning. Plastic changes have been reported in the visual cortex in resting state (Liu et al, 2007) and imaginary, tactile, and auditory tasks (Noppeney, 2007;Cattaneo et al, 2008), and in the early sensory areas of spared modalities following visual deprivation in early life (Bavelier and Neville, 2002). Thus, plasticity may lead to changes in cortical thickness in the early blind.…”
Section: Introductionmentioning
confidence: 99%
“…While congenitally blind subjects exhibit lower cortical volume in both frontal areas (BA 44, 45) and visual areas (BA 17,18) 48 , compared to a control population, functional connectivity between frontal areas (parts of BA 44, 45, and 47) and occipital areas is stronger in early blind 49 .…”
Section: Visual Activation (And Rems) In Blind Subjectsmentioning
confidence: 92%